KAJI EKSPERIMEN PERBAIKAN CACAT RONGGA BENDA CORAN MATERIAL FC 250 MELALUI PROSES PENGELASAN BERBASIS ELEKTRODA NIKEL - Hidayat, Reza Yadi; Soetopo, Antonius Adi; Muslim, Dede Buchori; Nahrowi, Muhammad; Khairani, Syifa (Jurusan Teknik Mesin Fakultas Sains dan Teknik Universitas Bangka Belitung, 2024)
Based on the case study in the field, it was found that the casting product had surface defects in the form of cavities and was then repaired using a nickel electrode-based welding method. This repair was carried out to close the cavity defects so that a perfect casting shape was obtained. The material that has been welded has a different hardness from the base material, making it difficult to machining. This study aims to analyze the effect of welding on the ability of gray cast iron material that has been welded in terms of cutting tool wear and chip formation. The sample used was made of gray cast iron with a weld bead on its surface. Welding used a CIN-1 nickel electrode with the SMAW (shielded metal arc welding) welding method. Cutting was carried out using a conventional milling process using an HSS dovetail cutter. Observations were made through hardness testing on the base material, PMZ (partially melted zone), and weld metal which was continued with microstructure testing, wear measurement and chips formed. Based on the results of observations of FC 250 material that was welded on the base material, the microstructure formed was pearlite with graphite in the form of thin and long flakes. The microstructure in PMZ is formed by martensite and carbide, while the microstructure in weld metal consists of an austenite matrix with even distribution of graphite particles. The microstructure formed affects the hardness value of the material. From the observation, the hardness between weld metal and base material is not much different, namely 219 HV and 224 HV. The hardness in PMZ is 385 HV.